Dental and maxillofacial features of Noonan Syndrome: Case series of ten patients. Issue 3 (March 2020) - Lutz, Jean-Christophe; Nicot, Romain; Schlund, Matthias; Schaefer, Elise; Bornert, Fabien; Fioretti, Florence; Ferri, Joël
Abstract: Noonan syndrome (NS) is a relatively common congenital multiple-anomaly syndrome, resembling Turner syndrome, but without chromosomal anomaly. Besides the unusual facies, the maxillofacial and dental features of patients with NS are not well-summarized in the literature. The aim of this study was to describe these features and propose specific treatment guidelines for practitioners involved in oral and maxillofacial care. A retrospective multicentric study was conducted of 14 patients who were referred for NS screening. In total, 10 patients were found to carry a mutation involved in NS or NS-related disorders. Fifty percent of the mutations affected PTPN11 . All patients presented with the typical extraoral features, such as macrocephaly, hypertelorism, ptosis, triangular face shape and ear dystrophy. Intraoral manifestations, including malocclusion (maxillary transversal deficiency, crossbite, anterior open-bite and class II malocclusion), dental anomalies (delayed eruption, agenesis and dystrophy, odontoma) and radiologic jaw lesions were identified in five out of 10 patients. These findings were searched in a review of the literature to obtain a comprehensive description of oral and maxillofacial features in patients with NS. The proposed treatment guidelines emphasize frequent coagulation anomalies that need to be considered prior to surgery. Early dental assessment and yearly follow-up with oral prophylaxis are recommended. Orthodontics and orthognathic surgery are also of primary importance in the management of NS patients.